Exploring access to, use of and benefits from population-oriented digital health services in Australia. (26th December 2020) - Foley, Kristen; Freeman, Toby; Ward, Paul; Lawler, Anthony; Osborne, Richard; Fisher, Matt
Summary: The provision of population-oriented, on-demand digital health services in many countries exemplifies the perceived utility of digital health services in supporting population health. Yet, limited knowledge exists regarding the equity of these services. Using mixed-method research, we recruited users of a health website and general practice patients to surveys ( n = 441) and telephone interviews ( n = 40). We contribute specific evidence investigating barriers to access, use and benefit from digital health services within an equity framework that incorporates social determinant factors, eHealth Literacy and trust. Our research highlights the foundational role of trust in predicting use, showcases which groups are unlikely to benefit from population-oriented digital health services, and proposes strategies to enhance the equity of these services. The theoretical framework we developed serves as a roadmap for future health promotion research and action by outlining the complex and interrelated pathways that can promote and threaten digital health equity.